Pengaruh Harga, Kualitas Produk, Kualitas Pelayanan, Dan Variasi Produk Terhadap Keputusan Pembelian Konsumen (Studi Pada Yellow Mart Sidorahayu, Kabupaten Malang) - Zulfrilanita, Amanda Zafirah; Wahono, Budi; Normaladewi, Andi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of price, product quality, service quality, and product variety on consumer purchasing decisions at Yellow Mart Sidorahayu, Malang Regency. The research employs a quantitative approach with descriptive and associative methods. The population consists of Yellow Mart consumers residing in Sidorahayu, with a total sample of 120 respondents determined using purposive sampling techniques. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results show that all independent variables (price, product quality, service quality, and product variety) have a positive and significant effect on purchasing decisions. These findings indicate that appropriate pricing strategies, good product quality, adequate service, and a diverse product variety can enhance consumer purchasing decisions. Keywords: Price, Product Quality, Service Quality, Product Variety, Purchasing Decision